Socially responsible public procurement - Juárez-Urquijo, Fernando (Anuario ThinkEPI, 2021)
We are on the verge of a generational changeover in public GLAM services (libraries, archives, museums, documentation centers), and predictions based on current contracting models indicate an increase in the amount of outsourcing. It is foreseeable that a cohort of new professionals will join the various administrations without being public employees, often carrying out permanent tasks. This note focuses on the problems of public procurement through outsourcing, on the opportunity for public administrations to promote sustainability, equity, and innovation if they use their great "purchasing power" with social responsibility criteria, and on the role of professional associations in the regulation of new labor ecosystems.